Diagnostic Accuracy of Body Mass Index (BMI) When Diagnosing Obesity in a Saudi Adult Population in a Primary Care Setting, Cross Sectional, Retrospective Study - Alammar M (Dove Medical Press, 2020)
Muath Alammar,1 Suad Alsoghayer,2 Kossay El-Abd,2 Abdullah Alkhenizan2 1Department of Family Medicine, Shaqra University, Shaqra, Saudi Arabia; 2Department of Family Medicine & Polyclinics, King Faisal Specialist Hospital and Research Centre, Riyadh, Saudi ArabiaCorrespondence: Abdullah AlkhenizanDepartment of Family Medicine & Polyclinics, King Faisal Specialist Hospital and Research Center, MBC 62, PO Box 3354, Riyadh 11211, Saudi ArabiaTel +966 11-4647272 Ext. 31860Fax +966 11- 4423055Email akhenizan@kfshrc.edu.saBackground: Obesity is a risk factor that leads to many chronic diseases and, unfortunately, its prevalence in Saudi Arabia is on the rise. To successfully manage obesity and its complications, patient must be accurately diagnosed. This study aims to investigate the diagnostic accuracy of body mass index (BMI) when diagnosing obesity within the Saudi population using body fat percentage (BF%) as the gold standard.Materials and Methods: This is a cross-sectional study that includes a calculated sample size of 942 subjects. Subjects were recruited from family medicine clinics that were linked to King Faisal Specialist Hospital and Research Centre (KFSH&RC) in Riyadh, Saudi Arabia from January 2005 to March 2016. BF% was estimated using DEXA scan. The diagnostic accuracy of BMI was assessed by using the WHO and the American Association of Clinical Endocrinologists and American College of Endocrinology (AACE/ACE) reference standard for obesity of BF% > 25% in men and > 35% for women.Results: Findings indicate, out of the study population, 29% of men and 53% of women are obese using BMI-defined obesity cut-off point 30 kg/m2. The prevalence of obesity was 83.9% and 97.3% in men and women, respectively, using BF%-defined obesity, which corresponds to BMI cut-off of 24 kg/m2. Even when considering the highest acceptable BF% based on the mean age of our participants (33% for men and 43% for women), the BMI cut-off to diagnose obesity should not exceed 27 kg/m2 among men and women in Saudi Arabia.Conclusion: The accuracy of BMI 30 kg/m2 to diagnose obesity among the Saudi population is limited. We have to lower the BMI cut-off point to improve its sensitivity as a screening tool for obesity. Our study suggests that the BMI cut-off point among Saudis and possibly the Arab population should not exceed 27 kg/m2 for both sexes.Keywords: obesity, BMI, DEXA, body fat, diagnostic accuracy, Saudi population